Computational Social Science: Computer-Supported Cooperative Work in the Social Media Era - Counts, Scott; Choudhury, Munmun De; Diesner, Jana; Gilbert, Eric; Gonzalez, Marta C.; Keegan, Brian; Naaman, Mor; Wallach, Hanna (CSCW'14, 2014)
With the widespread proliferation of social media tools such as Facebook and Twitter, the CSCW community has seen a growing interest among researchers to turn to records of social behavior from blogs, social media, and social networking sites, to study human social behavior. This nascent area, that has begun to be referred to in various research circles as “computational social science”, provides an exciting and promising development in the CSCW community. This panel brings together a host of researchers with varied disciplinary perspectives to investigate the potential and current state-of-the-art, as well as forthcoming challenges, practical and methodological issues that engender this emerging topic.